SEJARAH PEMBENTUKAN KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - Nurhasanah Nurhasanah; Isjoni Isjoni; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Rimba Melintang is one of the names of sub-districts located in Rokan Hilir Regency. Rimba Melintang Subdistrict was formed based on the Government Regulation of the Republic of Indonesia Number 33 of 1995 concerning Establishment of 13 sub-districts in the area of Tinggkat II Bengkalis Regency, Indragiri Hulu, Indragiri Hilir and Kampar in the Riau Province Region II territory established in Jakarta on September 4, 1995 with a population 33,237 people. Men were 16,826 and women were 16,411. Of the 13 sub-districts the name of the sub-district is the same as the capital city of only 2 sub-district, namely, the District of Rimba Melintang, the capital of Rimba Melintang, and the District of Minas, the capital of Minas. The objectives of this study are 1) To find out the history of the formation of Rimba Melintang Subdistrict, 2) To find out the legal basis of regional formation, 3) To determine the provisions of Rimba Melintang District as one of the expansion districts in Bangko District, 4) To find out the development of education Rimba Melintang Subdistrict from 2011 to the present, 5) To determine the economic development of Rimba Melintang District from 2011 to the present. This study used a qualitative research method with descriptive study. The results of this study indicate that the Rimba Melintang sub-district was originally only a village. Rimba Melintang is included in Bangko Subdistrict, whose capital is in Bagansiapiapi. In 1990 Bangko Subdistrict was very wide and had a large population, so the Bangko Subdistrict was divided into two, namely Bangko Subdistrict and Bangko Subdistrict, whose representatives were in Rimba Melintang. In 1995 the Melimba Melintang grew and the population grew, so that the Rimba Melintang was formed into a District.Keywords : Formation, District